The Sovereign’s Village: Memories of a Profound Journey into its Traditions and Peoples - Fonseca Reyes, Ángela Jasmín (Rastros Rostros, 2014)
This article, written in the style of a literary tale, arose as an alternative for sharing the results of the research study titled “The Cultural and Didactic Tradition of Social Sciences in the Sotaquirá Municipality”. This study fomented spaces for reflection on Sotaquirá’s cultural traditions within the classrooms of the Institución Educativa Pablo vi, and consolidated important spaces for learning around the prevailing ancestral knowledge in the region. The objective of this research study was to ethnographically rediscover the cultural traditions of country dwellers in the Sotaquirá municipality, in order to design alternative proposals for social science teaching in the secondary school classroom of the Colegio Pablo VI. This was achieved through substantial and pleasant fieldwork based on participant observation, occasional conversations, fraternal relationships, coexistence, and formal and informal interviews within a framework of pedagogical practice in the above school. These were the basic elements for understanding and describing the essence of certain cultural traditions that mostly still exist in the community of Sotaquirá. Finally, this research study contributed to the students attaching great value to aspects of their regional culture. Likewise, it strengthened intergenerational ties, showing the pressing need for the collective planning and creation of a communal educational project in parallel to the project conducted in the school.